Laxative use and 28-day mortality in critically ill sepsis patients: a retrospective cohort study using MIMIC-IV (v3.1) - Yan Liang; Feiyi Xu; Hao Zhang; Jiang Li; Wei Chen; Qilin Yang; Cheng Lin; Xiaomin Dong (Journal of Intensive Care)
Abstract Objective This study investigates the impact of four laxatives-Senna, Docusate Sodium, Polyethylene Glycol, and Lactulose on 28-day mortality, ICU-free days, ventilator-free days, bowel recovery, and Clostridium difficile (C-diff) infection in critically ill sepsis patients to identify optimal bowel management strategies for improving survival and recovery. Methods Using the MIMIC-IV database (v3.1), we analyzed 7163 ICU sepsis patients (median age: 67.5 years; 63% male), assessing 28-day mortality, ICU-free days, vasopressor-free days, ventilator-free days, bowel sound recovery, and C-diff incidence, with propensity score matching and multivariable adjustments for confounders, alongside subgroup analyses by sex, age, Charlson Comorbidity Index, and Sequential Organ Failure Assessment score. Results Docusate Sodium was associated with significantly lower 28-day mortality (adjusted HR: 0.43; 95% CI 0.36–0.52), more ICU-free days, and better bowel recovery compared to Senna, while Lactulose was linked to higher mortality (adjusted HR: 1.82; 95% CI 1.45–2.27), fewer ICU-free days, and increased C. difficile risk, with subgroup analyses confirming these trends across sex, age, and comorbidity strata. Conclusion Docusate sodium appears to be a safer and more effective bowel management option for critically ill patients with sepsis. In contrast, the association between lactulose use and adverse outcomes may primarily reflect the severity of underlying liver disease rather than a direct drug effect. These findings underscore the importance of individualized laxative selection based on patients’ clinical context in critical care practice.